2018
DOI: 10.1007/s00268-018-4614-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Early and Long‐Term Oncologic Outcomes After Converted Laparoscopic Resection Compared to Primary Open Surgery for Rectal Cancer

Abstract: Conversion to open surgery does not impair short-term outcomes and does not jeopardize 5-year survival in patients with rectal cancer when compared to primary open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 57 publications
3
8
0
1
Order By: Relevance
“…41 In our study we observed no differences between overall survival and disease-free survival between the 2 groups-a finding in line with several authors, 36,43 but different from those reporting a negative impact of conversions on long-term oncologic outcomes. 8,9,35 When survival was analyzed according to the location of the tumor (colon or rectum), we observed poorer survival in patients undergoing conversion in resections of the colon, although this did not reach statistical significance (P = 0.061), a result which is consistent with that from other studies. 36,43 There are various reasons which may explain the negative impact of conversions on oncologic outcomes.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…41 In our study we observed no differences between overall survival and disease-free survival between the 2 groups-a finding in line with several authors, 36,43 but different from those reporting a negative impact of conversions on long-term oncologic outcomes. 8,9,35 When survival was analyzed according to the location of the tumor (colon or rectum), we observed poorer survival in patients undergoing conversion in resections of the colon, although this did not reach statistical significance (P = 0.061), a result which is consistent with that from other studies. 36,43 There are various reasons which may explain the negative impact of conversions on oncologic outcomes.…”
Section: Discussionsupporting
confidence: 85%
“…Some authors have reported a negative impact of conversion on overall and disease-free survival while others have found no such differences. 8,9,[35][36][37][38] For this reason, we studied the risk factors associated with conversion to open surgery and their impact on operative morbidity and long-term oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Por lo que aconsejan, intentar el abordaje laparoscópico incluso en aquellos pacientes con cáncer de recto con factores preoperatorios de riesgo para la conversión 67 .…”
Section: Tasas De Conversiónunclassified